CTX-M-15-Producing E. coli Isolates from Food Products in Germany Are Mainly Associated with an IncF-Type Plasmid and Belong to Two Predominant Clonal E. coli Lineages - Irrgang, Alexandra; Falgenhauer, Linda; Fischer, Jennie; Ghosh, Hiren; Guiral, Elisabet; Guerra, Beatriz; Schmoger, Silvia; Imirzalioglu, Can; Chakraborty, Trinad; Hammerl, Jens A.; Käsbohrer, Annemarie (Frontiers in Microbiology, 2017)
Extended-spectrum beta-lactamases (ESBL) mediating resistance to 3rd generation cephalosporins are a major public health issue. As food may be a vehicle in the spread of ESLB-producing bacteria, a study on the occurrence of cephalosporin-resistant E. coli in food was initiated. A total of 404 ESBL-producing isolates were obtained from animal-derived food samples (e.g. poultry products, pork, beef and raw milk) between 2011 and 2013. As CTX-M-15 is the most abundant enzyme in ESBL-producing E. coli causing human infections, this study focusses on E. coli isolates from food samples harboring the blaCTX-M-15 gene. The blaCTX-M-15 gene was detected in 5.2% (n=21) of all isolates. Molecular analyses revealed a phylogenetic group A ST167 clone that was repeatedly isolated from raw milk and beef samples over a period of six months. The analysis indicates that spread of CTX-M-15-producing E. coli in German food samples was associated with a multireplicon IncF (FIA; FIB; FII) plasmid and additional antimicrobial resistance genes such as aac(6)-Ib-cr, blaOXA-1, catB3, different tet-variants as well as a class 1 integron with an aadA5/dfrA17 gene cassette. In addition, four phylogenetic group A ST410 isolates were detected. Three of them carried a chromosomal copy of the blaCTX-M-15 gene and a single isolate with the gene on a 90 kb IncF plasmid. The blaCTX-M-15 gene was always associated with the ISEcp1 element. In conclusion, CTX-M-15-producing E. coli were detected in German food samples. Among isolates of different matrices, two prominent clonal lineages, namely A-ST167 and A-ST410, were identified. These lineages may be important for the foodborne dissemination of CTX-M-15-producing E. coli in Germany. Interestingly, these clonal lineages were reported to be widely distributed and especially prevalent in isolates from humans and livestock. Transmission of CTX-M-15-harboring isolates from food-producing animals to food appears probable, as isolates obtained from livestock and food samples within the same time period exhibit comparable characteristics as well as to isolates detected from human. However, the routes and direction of transmission need further investigation.